Non‐negligible rate of needle tract seeding after endoscopic ultrasound‐guided fine‐needle aspiration for patients undergoing distal pancreatectomy for pancreatic cancer. Issue 5 (13th February 2020) - Yane, Kei; Kuwatani, Masaki; Yoshida, Makoto; Goto, Takuma; Matsumoto, Ryusuke; Ihara, Hideyuki; Okuda, Toshinori; Taya, Yoko; Ehira, Nobuyuki; Kudo, Taiki; Adachi, Takeya; Eto, Kazunori; et al.
Abstract : Background and aims: Needle tract seeding after preoperative endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) for pancreatic body and tail cancer has been reported. This study aimed to investigate the long‐term outcomes, including the needle tract seeding ratio, of patients undergoing distal pancreatectomy for pancreatic body and tail cancer diagnosed preoperatively by EUS‐FNA. Methods: This retrospective, observational cohort study assessed patients from three university hospitals and 11 tertiary referral centers. All patients who underwent distal pancreatectomy for invasive cancer of the pancreatic body and tail between January 2006 and December 2015 were identified and reviewed. Needle tract seeding rate, recurrence‐free survival (RFS), and overall survival (OS) were evaluated. Results: Of the 301 total patients analyzed, 176 underwent preoperative EUS‐FNA (EUS‐FNA group) and 125 did not (non‐EUS‐FNA group). The median follow‐up periods of the EUS‐FNA group and non‐EUS‐FNA group were 32.8 and 30.1 months. Six patients (3.4%) in the EUS‐FNA group were diagnosed as having needle tract seeding. The 5‐year cumulative needle tract seeding rate estimated using Fine and Gray's method was 3.8% (95% CI 1.6–7.8%). The median RFS or OS was not significantly different between the EUS‐FNA group and the non‐EUS‐FNA group (23.7 vs 16.9 months: P = 0.205; 48.0 vs 43.9 months: P = 0.392). Conclusion: Although preoperative EUS‐FNA for pancreatic body and tail cancer has no negative effect on RFS or OS, needle tract seeding after EUS‐FNA was observed to have a non‐negligible rate. (UMIN000030719)